PERSEPSI ANAK ASUH TERHADAP KEGIATAN PEMBINAAN DIPANTI ASUHAN YLBMI DESA PANDAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - daryanto, Riki daryanto Riki; Bahar, Aswandi Bahar Aswandi; ', Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: This study aims to determine the perception of student to building academic activities at Panti Asuhan YLBMI Pandau Jay, siak Kampar. The formulation of the problem in this study is that what is the students perception of the building academic activities at Panti Asuhan YLBMI Pandau Jaya, Siak, kampar? This is a descriptive study with a quantitative approach which aims to describe the results of research by the numbers. The sampling technique used is sampling techniquesom. Data collection techniques in this study is the questionnaire of 43 items statement. data analysis showed that the perception of student to the building of academic activities in term of religious formation activity indicator at Panti Asuhan YLBMI was quite good with an average percentage score of 60.918% over the moral and physical development. This means that the student argue that the building of academic activitiesat Panti asuhan is usefull.Key Words: Development activities, foster children, orphanage